Sistem POS Nobel Press Berbasis Web Menggunakan Metode Agile dengan Teknologi Progressive Web Application - Agunawan Agunawan; Aulyah Zakilah Ifani; Andi Ircham Hidayat; Nurkhalik Wahdanial Asbara (Journal of Information System Research (JOSH), 2025)
This research aims to develop a web-based Nobel Press Point of Sales (POS) system that is responsive and adaptive to user needs. The problem-solving approach in this study focuses on the development of a web-based Point of Sales (POS) system as a solution for the digitization of transactions at Nobel Press. The Agile method was chosen so that the development process can be carried out gradually and flexibly, adapting to the needs of dynamic users. The results of this study show that the application of Progressive Web Application (PWA) technology in the POS system for Nobel Press provides significant advantages, such as better accessibility and transaction efficiency, even in conditions without an internet connection and the development of a web-based Point of Sales (POS) system at Nobel Press has succeeded in creating an effective solution for digitizing book sales transactions. The test results showed that the system was able to perform key functions well, including stock management, sales transactions, and real-time reporting.